Characterization of discontinuous ventilation cycles in nymphal Ixodes scapularis - Samantha Schofield; Jane S. Waters; Y.M. Nuwan D.Y. Bandara; Jannelle Couret (PLoS ONE, 2026)
Three-host Ixodid ticks, obligate blood-feeding Acari Parasitiformes, spend the majority of their lives off of hosts. They rely on morphological, physiological, and behavioral adaptations to address the compromise between water loss and obtaining oxygen sufficient to meet metabolic needs. Here, we characterize the patterns of ventilation of the blacklegged tick, Ixodes scapularis , providing the first measurements for Ixodes, and furthering understanding of the physiology of a medically important vector of tick-borne disease. Measuring CO 2 output of I. scapularis nymphs through a flow-through respirometry system, we confirm discontinuous ventilation in nymphal I. scapularis , describe discontinuous ventilation cycles (DVCs), and explore the basis of intraspecific variation rates of CO 2 emission. Both the frequency of the ventilation cycle and the magnitude of CO 2 emission bursts varied based on the developmental environment of the nymphs, all F1 laboratory-reared or collected from the wild. We discuss this initial measurement of DVCs in nymphal I. scapularis in comparison to other species in Ixodidae as well as the factors which have been shown to modulate the frequency of the ventilation cycles within other species.